2022
DOI: 10.3389/fimmu.2021.786666
|View full text |Cite
|
Sign up to set email alerts
|

Lactylated Histone H3K18 as a Potential Biomarker for the Diagnosis and Predicting the Severity of Septic Shock

Abstract: ObjectiveTo date, there are no studies regarding the lactylation profile and its role in critically ill patients. Thus, we aimed to examine expression of histone H3 lysine 18 (H3K18) lactylation and its role in patients with septic shock.MethodsThirteen healthy volunteers and 35 critically ill patients from the Department of Surgical Intensive Care Medicine, Beijing Hospital were enrolled in our study. Baseline information and clinical outcomes were obtained prospectively. Lactylation levels of all proteins an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
39
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(42 citation statements)
references
References 71 publications
(97 reference statements)
2
39
0
1
Order By: Relevance
“…Utilizing clinical samples from lean and obese individuals, we observed a strong, positive relationship between fasting plasma lactate levels and skeletal muscle lactylation ( Figure 1C ). Chu et al ( Chu et al, 2021 ) previously reported that circulating lactate was associated with histone lactylation in the peripheral blood mononuclear cell (PBMC) of healthy and septic individuals ( Chu et al, 2021 ). Despite in vivo results providing critical physiological relevance, they unfortunately do not prove insight into causation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Utilizing clinical samples from lean and obese individuals, we observed a strong, positive relationship between fasting plasma lactate levels and skeletal muscle lactylation ( Figure 1C ). Chu et al ( Chu et al, 2021 ) previously reported that circulating lactate was associated with histone lactylation in the peripheral blood mononuclear cell (PBMC) of healthy and septic individuals ( Chu et al, 2021 ). Despite in vivo results providing critical physiological relevance, they unfortunately do not prove insight into causation.…”
Section: Discussionmentioning
confidence: 99%
“…The goal of the current study was to determine if lactylation was present in human skeletal muscle utilizing a pan anti-Kla antibody commonly used to identify lactylation in other cell types ( Zhang et al, 2019 ; Chu et al, 2021 ; Cui et al, 2021 ; Hagiharai et al, 2021 ; Jiang et al, 2021 ; Meng et al, 2021 ). The confirmation of lactate-induced lactylation in human skeletal muscle advocates for future research to identify the specific proteins that undergo lactylation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Clinical trials have shown similar findings. In a study of 13 healthy volunteers and 35 critically ill patients with septic shock, Chu, X et al found that H3K18la may reflect the severity of critical illness and presence of infection, suggesting that H3K18la may have a significant impact on the balance of inflammation in sepsis ( Chu et al, 2021 ). In addition, Irizarry-C et al showed that when lacking B-cell adapter for PI3K (BCAP), macrophages show impaired lactate production and also exhibit reduced histone lactylation and lower tissue repair gene expression, which results in blunting their reparative transition ( Irizarry-Caro et al, 2020 ).…”
Section: Lactylation and Diseasesmentioning
confidence: 99%
“…7 Later studies have shown that histone lactylation plays key regulatory roles under a variety of biological conditions, such as cell state transition, 9 cell reprogramming, 10 neuronal excitation, 11 tumorigenesis, 12,13 glucose metabolism, 14 and so on. [15][16][17][18] The discovery of lactylation greatly extends our understanding of the functions of lactate and implies broad involvement of this modication in diverse biological processes, 19,20 given the widespread existence and high concentrations of L-lactate in mammals.…”
Section: Introductionmentioning
confidence: 99%